Employee Competence, Service Quality, and Job Satisfaction as Predictors of Organizational Commitment: Evidence from Indonesia’s Railway Sector - Fitriani, Aprilya; Fauziah, Fauziah (FEB Universitas Mulawarman, 2025)
Understanding the factors that shape organizational commitment remains a central concern in organizational and human resource management research, particularly in public and highly regulated organizations. However, empirical evidence on the role of service quality and job satisfaction, alongside employee competence, in influencing organizational commitment within state-owned transportation organizations remains limited. This study addresses this gap by examining the effects of competence, service quality, and job satisfaction on organizational commitment within a state-owned railway organization. Using a quantitative causal design, data were collected from 127 permanent employees of PT Kereta Api Indonesia (Persero) Daop 9 Jember through a structured questionnaire and analyzed using multiple linear regression. The findings reveal that competence has a negative and statistically insignificant effect on organizational commitment, indicating that competence alone does not automatically strengthen employee attachment in bureaucratic contexts. In contrast, service quality and job satisfaction have significant positive effects on organizational commitment, with job satisfaction emerging as the strongest predictor. The study contributes theoretically by explaining the conditional role of competence through person–job fit, skill underutilization, and institutional constraint perspectives. Practically, the findings highlight the importance of improving service quality, enhancing job satisfaction, and aligning competence development with job design and organizational systems to foster organizational commitment in public sector organizations